Public Procurement Reform in Latin America and the Caribbean - Schapper, Paul R.; Veiga Malta, Joao N. (World Bank, Washington, DC, 2017)
Procurement is a vital component of a country's public administration that links the financial system with economic and social outcomes. The state of government procurement greatly determines the governance and performance of community services and cuts across almost every area of planning, program management, and budgeting. Managing up to 20 percent of gross domestic product, a public procurement system that optimizes value-for-money has wide-ranging national benefits. On the other hand, weaknesses in procurement management under-deliver social services and increase sovereign risk for foreign investment. The analysis raises significant considerations about whether the development agencies, by promoting only a traditional model of procurement, are keeping pace with the changing needs of modern government. A refocus of procurement legislation and regulation in terms of standards and results rather than procedures would seem to represent a better match for modern entities. This would represent a significant cultural shift in the administration of procurement in these jurisdictions, and would require a major shift in the monitoring, evaluation and audit of this function. It would also have major implications for its professionalization.